Double-blind, Randomized, Placebo-controlled Trial With N-acetylcysteine for Treatment of Severe Acute Respiratory Syndrome Caused by Coronavirus Disease 2019 (COVID-19). (23rd September 2020) - de Alencar, Julio Cesar Garcia; Moreira, Claudia de Lucena; Müller, Alicia Dudy; Chaves, Cleuber Esteves; Fukuhara, Marina Akemi; da Silva, Elizabeth Aparecida; Miyamoto, Maria de Fátima Silva; Pinto, Vanusa Barbosa; Bueno, Cauê Gasparotto; Lazar Neto, Felippe; Gomez Gomez, Luz Marina; Menezes, Maria Clara Saad; et al.
Abstract: Background: A local increase in angiotensin 2 after inactivation of angiotensin-converting enzyme 2 by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may induce a redox imbalance in alveolar epithelium cells, causing apoptosis, increased inflammation and, consequently, impaired gas exchange. We hypothesized that N-acetylcysteine (NAC) administration could restore this redox homeostasis and suppress unfavorable evolution in patients with coronavirus disease 2019 (COVID-19). Methods: This was a double-blind, randomized, placebo-controlled, single-center trial conducted at the Emergency Department of Hospital das Clínicas, São Paulo, Brazil, to determine whether NAC in high doses can avoid respiratory failure in patients with COVID-19. We enrolled 135 patients with severe COVID-19 (confirmed or suspected), with an oxyhemoglobin saturation <94% or respiratory rate >24 breaths/minute. Patients were randomized to receive NAC 21 g (~300 mg/kg) for 20 hours or dextrose 5%. The primary endpoint was the need for mechanical ventilation. Secondary endpoints were time of mechanical ventilation, admission to the intensive care unit (ICU), time in ICU, and mortality. Results: Baseline characteristics were similar between the 2 groups, with no significant differences in age, sex, comorbidities, medicines taken, and disease severity. Also, groups were similar in laboratory tests and chest computed tomography scan findings. Sixteen patients (23.9%) in the placebo group received endotracheal intubation and mechanical ventilation, compared with 14 patients (20.6%) in the NAC group ( P  = .675). No difference was observed in secondary endpoints. Conclusions: Administration of NAC in high doses did not affect the evolution of severe COVID-19. Clinical Trials Registration: Brazilian Registry of Clinical Trials (REBEC): U1111-1250-356 (http://www.ensaiosclinicos.gov.br/rg/RBR-8969zg/ ). Abstract : We designed a double-blind, randomized, placebo-controlled trial to determine whether high-dose N-acetylcysteine could prevent respiratory failure in patients with severe acute respiratory syndrome caused by coronavirus disease 2019 (COVID-19); however, no difference was observed between the placebo and experimental groups.